Parasitic assemblages on leafminers: a comparison of structure and function among host Orders - Salvo, Silvia Adriana (2011)
In this study we ask whether parasitic complexes of leafminers display differences associated to host order, by comparing species number, taxonomic composition, parasitism rates and host ranges in parasitoid assemblages associated with lepidopteran and dipteran leafminers, in Chaco Serrano woodlands, central Argentina. Parasitoid assemblage size did not significantly differ between host orders, but dipteran hosts suffered higher parasitism rates. Lepidopteran hosts recruited a higher proportion of species and individuals of Braconidae, whereas dipteran leafminers were attacked by a higher proportion of Pteromalidae. We found clear effects of host taxonomic affiliation on the associated parasitoid fauna.